Two new species of Tarenaya (Cleomaceae) from Brazil - Neto, Raimundo Luciano Soares; Barbosa, Maria Regina De Vasconcellos; Roalson, Eric H. (Phytotaxa, 2018)
Two new endemic species of Tarenaya from Brazil are described and illustrated here. These species have been previously recognized, but their names were never validly published. They resemble each other by the armed petioles, corymbiform racemes, small flowers and sessile to subsessile mature capsules with deflexed and persistent sepals. Tarenaya curvispina is characterized by the curved stipular spines, serrulate-ciliate margins of the leaflets, and ascending fruits, while T. pernambucensis is characterized by being puberulent-glandular throughout, straight stipular spines, the margin of leaflets entire, and ciliate and deflexed fruits.